MANAJEMEN LINEN PADA RUMAH SAKIT SITI KHODIJAH SIDOARJO TAHUN 2016 - Nurfarida Safitri; A. T. Diana Nerawati; Demes Nurmayanti (GEMA LINGKUNGAN KESEHATAN, 2016)
Linen is a material or a device made of fabric or woven. Linen from the hospital is not used directly in a treatment, yet the effect can be seen when its management is not good. Linen from the hospital will lead to disease transmission through crossinfection with linen as the medium of transmission of the disease. The purpose of this study was to determine the management of linen in laundry unit at Siti Khodijah Hospital, Sidoarjo.This is a descriptive research describing the management of linen which includes the handling of linens, tools and materials, linen laundry, clean linen quality and the behavior of linen management officer in laundry unit of Siti Khodijah Hospital, Sidoarjo. The results showed that the stage of collecting, transporting, sorting and washing did not meet the standard by 60%, 70%, 58% and 70% respectively. While drying and ironing, storage, distribution and laundry met the standard with the percentage of 80%, 75%, 80% and 75% respectively. The quality of clean linen from bacteriological aspect was qualified yet physically ineligible. The behavior of linen management officer was in "good" category (66.7%). In conclusion, the management of linen in laundry unit of Siti Khodijah hospital did not meet the standard (70%). As an improvement, the hospital should have linen management training for officers, provide job descriptions or written and clear work division in unit laundry, pay more attention to the compliance of the officers in the use of personal protective equipment and compliance with Standard Operating Procedure (SOP) of hand washing. Officers should conduct physical checks on and maintain the cleanliness of the clean linen in the distribution process. Keywords: Assessment, Linen management, Clean linen quality